Seasonal Dynamics of Dissolved Iron on the Antarctic Continental Shelf: Late‐Fall Observations From the Terra Nova Bay and Ross Ice Shelf Polynyas. Issue 10 (17th October 2022) - Sedwick, P. N.; Sohst, B. M.; O'Hara, C.; Stammerjohn, S. E.; Loose, B.; Dinniman, M. S.; Buck, N. J.; Resing, J. A.; Ackley, S. F.
Abstract: Over the Ross Sea shelf, annual primary production is limited by dissolved iron (DFe) supply. Here, a major source of DFe to surface waters is thought to be vertical resupply from the benthos, which is assumed most prevalent during winter months when katabatic winds drive sea ice formation and convective overturn in coastal polynyas, although the impact of these processes on water‐column DFe distributions has not been previously documented. We collected hydrographic data and water‐column samples for trace metals analysis in the Terra Nova Bay and Ross Ice Shelf polynyas during April–May 2017 (late austral fall). In the Terra Nova Bay polynya, we observed intense katabatic wind events, and surface mixed layer depths varied from ∼250 to ∼600 m over lateral distances <10 km; there vertical mixing was just starting to excavate the dense, iron‐rich Shelf Waters, and there was also evidence of DFe inputs at shallower depths in the water column. In the Ross Ice Shelf polynya, wind speeds were lower, mixed layers were <300 m deep, and DFe distributions were similar to previous, late‐summer observations, with concentrations elevated near the seafloor. Corresponding measurements of dissolved manganese and zinc, and particulate iron, manganese, and aluminum, suggest that deep DFe maxima and some mid‐depth DFe maxima primarily reflect sedimentary inputs, rather than remineralization. Our data and model simulations imply that vertical resupply of DFe in the Ross Sea occurs mainly during mid‐late winter, and may be particularly sensitive to changes in the timing and extent of sea ice production. Plain Language Summary: The Ross Sea is among the most productive areas on the Antarctic continental shelf. Here, primary production during the austral summer season is limited by the availability of dissolved iron (DFe), an essential micronutrient. A major source of DFe to Ross Sea surface waters is thought to be deep convective mixing, driven by strong, cold katabatic (offshore) winds and associated sea ice formation during austral winter (∼May–September). This mixing is assumed to deliver DFe‐rich bottom waters to the surface, particularly in coastal polynyas, where sea ice is formed and exported northwards. However, the impact of winter mixing on the distribution of DFe has not been previously documented in the Ross Sea. We report such observations from the Terra Nova Bay polynya (TNBP) and Ross Ice Shelf polynya (RISP) at the onset of winter (late April to late May) 2017. In the TNBP, intense katabatic winds and vigorous sea ice formation drove convective mixing that was penetrating into dense, DFe‐rich bottom waters. In the RISP, with milder local winds and less sea ice formation, vertical mixing had not reached DFe‐rich deep waters. Our results indicate that deep mixing does indeed supply substantial DFe to Ross Sea surface waters, although primarily in mid‐late winter (∼June–September). Key Points: Late‐fall observations from two Ross Sea polynyas reveal variability in the extent of vertical mixing and distributions of dissolved iron In Terra Nova Bay, katabatic winds and sea ice formation drove deep convective mixing that had extended into dense, iron‐rich Shelf Waters Vertical mixing was less advanced in the Ross Ice Shelf polynya, suggesting that vertical resupply of iron mainly occurs later in winter